1996
DOI: 10.2135/cropsci1996.0011183x003600040027x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Four Spring Wheat Cultivars to Drought Stress

Abstract: Identification and understanding of the mechanism of drought tolerance in wheat (Triticum aestivum L.) cultivars has long been a major goal of plant breeders. Our objective was to determine if leaf water potential, osmotic potential, yield, and yield components could be used to differentiate apparent drought tolerance among the cultivars. Four spring wheat cultivars (Giza 165, Gemmiza I, Klassic, and SPHE3) from different geographic regions were grown in a greenhouse at 20/ 15°C with 12 h of daylight augmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 0 publications
5
24
0
1
Order By: Relevance
“…Souza and Soares Sobrinho (1983) also reported that the BH-1146 cultivar adapted better to water stress. Moustafa et al (1996) and Villareal et al (1998) showed that certain cultivars react better under water stress. The Cocoraque cultivar highest tiller/total yield ratio was 11.6%.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Souza and Soares Sobrinho (1983) also reported that the BH-1146 cultivar adapted better to water stress. Moustafa et al (1996) and Villareal et al (1998) showed that certain cultivars react better under water stress. The Cocoraque cultivar highest tiller/total yield ratio was 11.6%.…”
Section: Methodsmentioning
confidence: 97%
“…They found that irrigation could increase yield up to 4.7 times in years with low rainfall during the plant growth period. Reduction in grain yield also depends on the genotype cultivated and the physiological stage of the plants under stress (Hobbs, 1953 ;Robins and Domingo, 1962;Singh et al, 1979;Sairam et al, 1990;Blum et al, 1990;Thompson e Chase, 1992;Moustafa, et al, 1996;Ravichandran e Mungse, 1997;Villareal et al, 1998;Guerra e Antonini, 1996). Souza and Soares Sobrinho (1983) found that the BH-1146 cultivar had more stable yield under the most adverse environmental conditions due to its tolerance to toxic acid soils, drought, temperature variations and different sunlight conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A major limitation has been the lack of a technique to identify drought tolerance that is repeatable and that can be used in populations where genetic segregation is present. The multitude of factors involved in plant response to water stress makes it difficult to provide a test of drought tolerance (MOUSTAFA et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Several workers reported also wheat genotypic differences under both drought stress and non-stress conditions in number of spikes/plant (Mosaad et al 1995, Moustafa et al 1996, and Al-Naggar et al 2004 and plant height ( Sharma and Bhargava 1996, Khanna et al 1986and Al-Naggar et al 2004.…”
Section: Mean Performance Of M 2 Bulks and Their Parentmentioning
confidence: 97%
“…To start a proper wheat breeding program for improving drought tolerance, the source populations should possess sufficient genetic variability amenable for selection. Unfortunately, with present distribution of improved high yielding, pure line cultivars in all of the world's wheat growing areas, selection from established cultivars would rarely isolate a new genotype (Poehlman and Sleper, 1995). Two breeding procedures, i.e., mutation and hybridization are used to induce new genetic variation.…”
Section: Introductionmentioning
confidence: 99%